PEMANFAATAN DIGITAL MARKETING BAGI USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI KELURAHAN RENON KECAMATAN DENPASAR SELATAN, BALI - Ni Putu Andini Desiyanti Laksmi (Forum Manajemen, 2021)
Digital marketing is a promotional activity and market search through digital media online by utilizing various means such as social networking. The purpose of this research is to increase knowledge and skills about digital marketing, especially social media, for Small and Medium Enterprises (SMEs) business people to increase their sales and profits. Attended by UMKM participants from Renon Village, South Denpasar District, Bali, the methods used in this activity were; first, an explanation using a power point slide and an LCD projector; second, sharing experiences and discussions; and finally, the direct practice of creating social media accounts (Facebook and Instagram) and how to make them attractive to buyers (images, words, stories, etc.). The results show that some business actors are actively using social media as their promotional tool and they have not separated their online store accounts from their personal accounts, some other people use them occasionally, and the rest of the participants never use social media marketing due to a lack of technology skills. All participants showed great interest in using social media marketing on a continuous basis.